Perlindungan Hukum Merek Dagang di Indonesia - Meiske Lasut (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
This study aims to analyze the legal protection of company trademarks and the legal consequences of counterfeiting trademarks. Marks have an important role in trade traffic for both registered brand owners and consumers to be able to recognize the quality of the products used so that there is a need for protection of the mark. This research is a normative juridical research with an analytical perspective. Trademark protection appears after the mark is registered because UUMIG adheres to a constitutive principle where the right to a mark arises after registration, therefore the use of a mark without rights has legal consequences both civilly in the form of a lawsuit for compensation and criminally in the form of imprisonment and fines. The research results show that legal protection for trademarks in Indonesia and internationally is given after the mark is registered. This also applies to well-known brands for goods and services that are similar or not. The legal consequences of using a mark without rights are civil or criminal. Civil lawsuits for misuse of marks from unauthorized parties can be in the form of material or immaterial compensation, while criminal legal consequences can be in the form of imprisonment and fines.